Investigation on geometric parameter of floating platform movment using air pressure - Sharifah Hanisah Said Jamallulai (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
A floating platform in the air is widely used in the industry nowadays. This platform is use as the transportation medium for some industries or parties. The problem that always occure for transporting loads previously is the vibration that can affect the quality of the product. Therefore, the concept of non-contracting between surface of platform achieved almost zero friction can exten the life span of the produc this study is to investigate the geometric parameter of floating platform movement using air product